Evaluation of ampicillin plus ceftobiprole combination therapy in treating Enterococcus faecalis infective endocarditis and bloodstream infection - Simone Giuliano; Jacopo Angelini; Floriana Campanile; Paola Conti; Sarah Flammini; Alberto Pagotto; Francesco Sbrana; Luca Martini; Denise D’Elia; Mohd H. Abdul-Aziz; Menino O. Cotta; Jason A. Roberts; et al. (Scientific Reports)
Abstract Enterococcus faecalis is responsible for numerous serious infections, and treatment options often include ampicillin combined with an aminoglycoside or dual beta-lactam therapy with ampicillin and a third-generation cephalosporin. The mechanism of dual beta-lactam therapy relies on the saturation of penicillin-binding proteins (PBPs). Ceftobiprole exhibits high affinity binding to nearly all E. faecalis PBPs, thus suggesting its potential utility in the treatment of severe E. faecalis infections. The availability of therapeutic drug monitoring (TDM) for ampicillin and ceftobiprole has prompted the use of this drug combination in our hospital. Due to the time-dependent antimicrobial properties of these antibiotics, an infusion administration longer than indicated was chosen. From January to December 2020, twenty-one patients were admitted to our hospital for severe E. faecalis infections and were treated with this approach. We retrospectively analyzed their clinical characteristics and pharmacological data. Most patients achieved an aggressive PK/PD target (T > 4–8 minimum inhibitory concentration, MIC) when this alternative drug combination regimen was used. Our analysis included the study of E. faecalis biofilm production, as well as the kinetics of bacterial killing of ceftobiprole alone or in combination with ampicillin. Time-kill experiments revealed strong bactericidal activity of ceftobiprole alone at concentrations four times higher than the MIC for some enterococcal strains. In cases where a bactericidal effect of ceftobiprole alone was not evident, synergism with ampicillin and bactericidal activity were demonstrated instead. The prolonged infusion of ceftobiprole, either alone or with ampicillin, emerges as a valuable option for the treatment of severe invasive E. faecalis infections.